Five siRNAs Targeting Three SNPs May Provide Therapy for Three-Quarters of Huntington's Disease Patients - Pfister, Edith L.; Kennington, Lori; Straubhaar, Juerg; Wagh, Sujata; Liu, Wanzhou; DiFiglia, Marian; Landwehrmeyer, Bernhard; Vonsattel, Jean-Paul; Zamore, Phillip D.; Aronin, Neil (Current biology, 2009)
Among dominant neurodegenerative disorders, Huntington's disease (HD) is perhaps the best candidate for treatment with small interfering RNAs (siRNAs) [1–9]. Invariably fatal, HD is caused by expansion of a CAG repeat in the Huntingtin gene, creating an extended polyglutamine tract that makes the Huntingtin protein toxic [10]. Silencing mutant Huntingtin messenger RNA (mRNA) should provide therapeutic benefit, but normal Huntingtin likely contributes to neuronal function [11–13]. No siRNA strategy can yet distinguish among the normal and disease Huntingtin alleles and other mRNAs containing CAG repeats [14]. siRNAs targeting the disease isoform of a heterozygous single-nucleotide polymorphism (SNP) in Huntingtin provide an alternative [15–19]. We sequenced 22 predicted SNP sites in 225 human samples corresponding to HD and control subjects. We find that 48% of our patient population is heterozygous at a single SNP site; one isoform of this SNP is associated with HD. Several other SNP sites are frequently heterozygous. Consequently, five allele-specific siRNAs, corresponding to just three SNP sites, could be used to treat three-quarters of the United States and European HD patient populations. We have designed and validated selective siRNAs for the three SNP sites, laying the foundation for allele-specific RNA interference (RNAi) therapy for HD.